TEMAN TAPI MESRA HUMAS DAN WARTAWAN (Studi Kasus Strategi Hubungan Media di Bidang Humas dan Protokoler Universitas Ahmad Dahlan) - Muhammad Najih Farihanto (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
Teman tapi mesra, that’s the impression the relationship between PR and journalists. Why, because both of them have to establish good relations and mutual benefit in order to achieve their respective goals. With the role of public relations officer (PR), Ahmad Dahlan University as one of the Muhammadiyah’s higher education established a harmonious relationship with the media for the realization of organization goals. In this research showed that PR UAD has taken various strategies media relations activities to build relationships with journalist, but that is quite unfortunate PR UAD less an evaluation and follow-up of various in media relations activities that have been carried out. This research is a descriptive qualitative and using case studies as empirical issues raised regarding a case to be more focused on the object of study and be able to explain the objects around the study. In this research using interviews, document searches and direct observation in the data collection process.